The sustainable development of Heathrow Airport: model inter-comparison study. (8th February 2011) - Sabatino, Silvana Di; Solazzo, Efisio; Britter, Rex
Air quality modelling near airports has received attention due to the impact of emissions from aircrafts near ground level. This work is part of the model inter-comparison study undertaken for the Department of Transport in connection with air quality near Heathrow Airport. Results formed part of a submission to the UK government in July 2006. The Emissions and Dispersion Modelling System (EDMS) was used. Our contribution required the setting up and running of EDMS for Heathrow Airport and its surroundings to simulate the year 2002. NOX, NO2 and PM10 were chosen for the study; these being of particular concern.